2014
DOI: 10.1186/1742-4690-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Human protein Staufen-2 promotes HIV-1 proliferation by positively regulating RNA export activity of viral protein Rev

Abstract: BackgroundThe export of intron containing viral RNAs from the nucleus to the cytoplasm is an essential step in the life cycle of Human Immunodeficiency Virus-1 (HIV-1). As the eukaryotic system does not permit the transport of intron containing RNA out of the nucleus, HIV-1 makes a regulatory protein, Rev, that mediates the transportation of unspliced and partially spliced viral mRNA from the nucleus to the cytoplasm, thereby playing a decisive role in the generation of new infectious virus particles. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Activated microglia and macrophages associated with HIV-1 neuropathogenesis are known to release various proinflammatory molecules. Among them, tumor necrosis factor (TNF-α) and interleukin-1 (IL-1β) play a central role in neuroinflammation 52 54 . Hence, we measured cumulative levels of TNF-α and IL-1β in supernatants from MG-hBORGs by ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia and macrophages associated with HIV-1 neuropathogenesis are known to release various proinflammatory molecules. Among them, tumor necrosis factor (TNF-α) and interleukin-1 (IL-1β) play a central role in neuroinflammation 52 54 . Hence, we measured cumulative levels of TNF-α and IL-1β in supernatants from MG-hBORGs by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the early findings conducted in post-mortem tissue from HIV-infected individuals correlating both, viral replication and TNF-α transcription 73 . Similarly, IL-1β is also elevated in the CNS during HIV-1 infection 52 . In our study, we observed similar IL-1β release from HIV-1-infected MG-hBORG over the course of the culture consistent with previous work of our group showing variation of IL-1β expression and release by monocyte-derived macrophages throughout the course of HIV-1 infection 55 .…”
Section: Discussionmentioning
confidence: 96%
“…Infectious HIV‐1 particles were prepared by transfection of proviral DNA pNL‐ADA8 into HEK293T cells by calcium phosphate method. Culture supernatants were collected at intervals of 24 h post‐transfection, filtered through 0.45 μM syringe filter (Millipore, USA), precipitated using Polyethylene glycol (Kutner et al , ; Banerjee et al , ) and quantified by HIV‐1 p24 ELISA kit (Advanced BioScience Laboratories Inc, USA) according to the manufacturer's protocol. Cells were infected with 30 ng ml −1 of p24 equivalents of HIV.…”
Section: Preparation and Quantification Of Infectious Hiv‐1 (Ada8) Pamentioning
confidence: 99%
“…Interestingly, STAU1 only modulates Gag assembly once the tail of Gag has anchored into the plasma membrane suggesting that STAU1 may play a role in ensuring the RNP is delivered to the membrane [ 86 ]. STAU2 has also been shown to promote the activity of HIV-1 Rev protein in exporting vRNA from the nucleus, along with DExH-box helicase 9 (DHX9) and ArfGAP with FG repeats 1 (AGFG1) [ [89] , [90] , [91] ]. Together, these studies suggest that Staufen proteins play crucial roles in the transport of HIV-1 RNPs from the nucleus to the plasma membrane for viral particle formation.…”
Section: Do Cellular Rbps Participate In Viral Particle Assembly?mentioning
confidence: 99%